Thermal Behavior of Tacca leontopetaloides Starch-Based Biopolymer - Nurul Shuhada Mohd Makhtar; Miradatul Najwa Muhd Rodhi; Mohibah Musa; Ku Halim Ku Hamid (International Journal of Polymer Science)
Starch is used whenever there is a need for natural elastic properties combined with low cost of production. However, the hydrophilic properties in structural starch will decrease the thermal performance of formulated starch polymer. Therefore, the effect of glycerol, palm olein, and crude palm oil (CPO), as plasticizers, on the thermal behavior of Tacca leontopetaloides starch incorporated with natural rubber in biopolymer production was investigated in this paper. Four different formulations were performed and represented by TPE1, TPE2, TPE3, and TPE4. The compositions were produced by using two-roll mill compounding. The sheets obtained were cut into small sizes prior to thermal testing. The addition of glycerol shows higher enthalpy of diffusion in which made the material easily can be degraded, leaving to an amount of 6.6% of residue. Blending of CPO with starch (TPE3) had a higher thermal resistance towards high temperature up to 310°C and the thermal behavior of TPE2 only gave a moderate performance compared with other TPEs.